2009
DOI: 10.3109/09638280903204716
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of the central posteroanterior mobilization technique on pain and range of motion in patients with mechanical neck pain

Abstract: The clinical recommendation regarding the selection of the central PA mobilization technique for treating patients with central or bilateral mechanical neck pain is therefore arguably.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…PPT was proposed as the primary outcome measure because it was expected to be more sensitive to initial changes following treatment 8, 64,71 than resting pain (VAS). 32,33 Data were checked for normality prior to statistical analyses, which were performed per protocol. Descriptive statistics and counts were used to describe the sample.…”
Section: Discussionmentioning
confidence: 99%
“…PPT was proposed as the primary outcome measure because it was expected to be more sensitive to initial changes following treatment 8, 64,71 than resting pain (VAS). 32,33 Data were checked for normality prior to statistical analyses, which were performed per protocol. Descriptive statistics and counts were used to describe the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Vernon et al 14 and that by Hegedus et al 15 only included studies which examined the effects of joint mobilization and not those studies which combined joint mobilization with other interventions. Consequently, the primary purpose of this systematic review and meta-analysis was to examine the effects of a single session of joint mobilization in symptomatic subjects, performed at any spinal region, on changes in self-reported pain at rest and self-reported pain with the most painful movement.…”
Section: Introductionmentioning
confidence: 99%
“…Further, similar effects, decreased pain and increased motion, have been observed when mobilization was performed at the asymptomatic level (non-specific level) or at the symptomatic level (the specific level). 14 In addition, a third systematic review that included both randomized and non-randomized controlled trials concluded that a single session of spinal mobilization may have little or no clinically meaningful or lasting effect. 15 The study by…”
Section: Introductionmentioning
confidence: 99%
“…Mobilization is found to reduce pain, the aim of mobilization included enhancement of passive physiologic motions within painfree limit [16]. However there is not much significant difference seen in cervical rotation and shoulder range of motion when compared to the case study.…”
Section: Resultsmentioning
confidence: 89%
“…Only a single case report has been conducted to study the effect of manual therapy, however the author suggested further need of randomized trials to know the effect of manual therapy approach on post operated cancer patients. The rationale remains same unlike other approaches of manual therapy DISCUSSION study includes maitland mobilisation in central PA direction [16]. In head and neck cancer patients with range of motion restriction of neck and shoulder is one of common complication seen post surgery, Also, limited mouth opening due to pain and sutures is seen commonly in buccal mucosa and tongue cancer patients.…”
Section: Resultsmentioning
confidence: 99%